Desenvolvimento de biomateriais porosos acoplados a sistema carreadores: ácido zoledrônico encapsulado em lipossomas - Silva, Luana Patricia Bezerra (2022)
Hydroxyapatite (HAP) is a ceramic biomaterial widely used in applications related to bone grafting due to its properties very similar to bone. Although HAP is a material with notorious scientific advances, its application is difficult due to its microstructural configuration, which hinders the development and migration of bone cells, in addition, it also presents a difficult degradability. The combination of this material with other ceramics can generate an optimization in the final product. For this, HAP was combined with beta tricalcium-phosphate (BTCP) in order to speed up the degradation of the biomaterial and increase its porosity. Some alternatives were studied to optimize the HAP:BTCP formulation to improve porosity through the use of sacrificial materials (microcrystalline cellulose). Zoledronic acid encapsulated in liposomes coupled to ceramic pores was also used in order to improve cellular osteostimulation (osteoblasts and osteoclasts) and, thus, reduce the patient's clinical recovery time.To characterize the ceramics, X-ray diffraction, scanning electron microscopy and mercury porosimetry were performed, while zeta potential, dynamic light scattering and percentage of drug encapsulation were performed in liposomal vesicles. The results proved to be promising, since it was possible to optimize the amount of pores present in the bioceramics. The obtained liposomes were also validated through the analyses, with the used methodology it was possible to reach an encapsulation efficiency of 32.95% of the drug. The methodology used to couple the bioceramic to the liposome/AZ complex showed a promising result of 57,1% for HAP and 52,8% for BTCP.